Evaluation of Platelet Count among Women with Preeclampsia: A Case-Control Study from Pakistan - Saima Siddiq Choudhry, Mubashira Nasir Qureshi, Shagufta Jabbar, Kamran Ullah Khan, Sadaf Kashif, Marya Saadullah Khan (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare the platelet count in women with preeclampsia with that in women without preeclampsia. Methodology: A case–control study was conducted between July 2019 and March 2020 at Social Security Teaching Hospital Multan Road, Lahore. Total 60 preeclamptic female were the cases & an equal number of healthy pregnant women were the controls. Women with gestation period of 27 weeks or less, younger than 18 years and those with hypertension before 20 weeks of gestation were excluded from the study. Patients’ demographics, medical and surgical history, comorbidities, reproductive history, blood pressure and other related variables were recorded on a predefined proforma. Data analysis was done with SPSS version 26. Results: The mean platelet count of 360.54 ± 71.25 (range of 200-450) x 109 cells/L was observed in the control group while a mean platelet count of 202.74 ± 45.57 (range 90-350) x 109 cells/L was reported in the study group. A significant p value of 0.000 was observed. The platelet distribution width, % was high significantly in patients with preeclampsia compared to the control group (p = 0.05). Conclusion: We reported that patients with preeclampsia had significantly lower platelet count compared to the healthy pregnant women. Further large-scale studies should be conducted to observe the role of platelets in the progression of the disease. Keywords: hypertension, pregnancy, preeclampsia, platelets, PDW, mean platelet volume